APPLICATION OF THE MODEL INQUIRY LEARNING FOR EFFORTS TO IMPROVE ENGLISH LEARNING ACHIEVEMENT (A Case Study in Class XII IPA-3 MAN 2 Students in Odd Semester Academic Year 2019/2020) - Muzammil Muzammil (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
This research is intended to describe the Inquiry Learning (IL) Model in order to improve students' English learning achievement. The purpose of this study was to determine whether there was an increase in the English learning achievement of students in class XII IPA-3 Madrasah Aliyah Negeri 2 Pati, in the Odd Semester of the 2019/2020 Academic Year. The research subjects were 36 students of class XII IPA-3 Madrasah Aliyah Negeri 2 Pati. The research variables consisted of student variables (students' ability to solve questions) and teacher variables (planning and implementing learning by teachers in the classroom). The research was conducted in two cycles and each cycle consisted of four stages, namely: planning, implementing, observing and reflecting. Success indicators are determined when at least 75% of students achieve learning completeness after the Inquiry Learning (IL) Model is applied. From the research results, it was found that there was an increase in students' English learning achievement as indicated by: (1) the average student achievement in cycle I was 7.29, cycle II was 7.49 and cycle III cycle III was 8.81 ; (2) in the first cycle there were 22 students or 61.11% who completed the study; and those who did not complete were 14 students or 38.89%; in cycle II there were 26 students or 72.22% complete learning; and students who did not complete there were 10 students or 27.78%; and in cycle III there are 36 students or 100% complete learning; and there are no students who do not complete; and (3) completeness of classical learning in the first cycle is 61.11%; in cycle II classical completeness became 72.22%; while in cycle III it reached 100.00%. This means that the competency test / evaluation results in cycle I, cycle II and cycle III always increase. There is an increase in student activity during the learning process, both individually and in groups. Student response to the implementation of the Inquiry Learning (IL) Model is 85.22% (strongly agree or in the very high category.